2011
DOI: 10.1038/ki.2011.244
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of patients randomized to biocompatible or conventional peritoneal dialysis solutions show no difference in peritonitis or technique survival

Abstract: Peritonitis remains a common clinical problem for patients on peritoneal dialysis (PD). There are, however, retrospective studies with historical controls that suggest that biocompatible PD solutions may reduce the rates of peritonitis. We conducted a randomized controlled study comparing the use of biocompatible and conventional solutions, accumulating over 7000 patient-months experience. We included peritonitis episodes from patients who discontinued PD during the follow-up period. The study was powered to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 28 publications
5
28
0
2
Order By: Relevance
“…However, this finding should be interpreted with caution in light of the disproportionate number of peritonitis episodes between the two groups (biocompatible-ever, n=80; biocompatible-never, n=757), with small event numbers in each micro-organism category and analysis of organisms responsible for first peritonitis only. In contrast, an extended-recruitment RCT involving 267 participants with .7000 patient-months of follow-up found no significant overall difference in micro-organisms responsible for peritonitis (18). Similarly, the balANZ trial reported similar micro-organism profiles between the treatment and control groups, except for a significantly reduced risk of nonpseudomonal gram-negative peritonitis with the use of neutral-pH, low-GDP PD solution (36).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, this finding should be interpreted with caution in light of the disproportionate number of peritonitis episodes between the two groups (biocompatible-ever, n=80; biocompatible-never, n=757), with small event numbers in each micro-organism category and analysis of organisms responsible for first peritonitis only. In contrast, an extended-recruitment RCT involving 267 participants with .7000 patient-months of follow-up found no significant overall difference in micro-organisms responsible for peritonitis (18). Similarly, the balANZ trial reported similar micro-organism profiles between the treatment and control groups, except for a significantly reduced risk of nonpseudomonal gram-negative peritonitis with the use of neutral-pH, low-GDP PD solution (36).…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, data from randomized controlled trials (RCTs) are conflicting. Of the 13 RCTs that reported peritonitis (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), only 2 showed significant benefit with the use of biocompatible PD solutions (19,22); the remainder reported a neutral effect. However, most trials examined peritonitis as a secondary outcome only; they can therefore not be regarded as providing definitive evidence.…”
Section: Introductionmentioning
confidence: 99%
“…In a 6-month extension substudy of one of those trials (35), which involved 57 of the original 106 participants, peritonitis rates were significantly lower in the biocompatible group than in the control group (0.24 episodes vs 0.63 episodes per patient-year respectively, p < 0.05). However, longer-term follow-up of an augmented number of trial participants in another randomized controlled trial reported by Srivastava et al (44) did not demonstrate a significant difference in peritonitis rates between the biocompatible and control groups (0.52 episodes vs 0.45 episodes per patient-year respectively, p = 0.82). In that trial, 86% of patients in the intervention arm used Physioneal (Baxter Healthcare Corporation, Deerfield, IL, USA), which contains appreciably higher levels of GDPs than Balance does (28,43,45,46) and therefore may have been less effective at preserving peritoneal host defenses against infection.…”
Section: Pdimentioning
confidence: 93%
“…Icodextrin use is associated with clear clinical benefits with respect to UF (19) and metabolic parameters (20), but its signal with respect to inflammatory markers may not be entirely benign (21). It is not clear that the results of balANZ would apply equally to neutral-pH solutions in which the concentration of GDPs may be higher, and that argument has been used to explain the lack of an impact on either residual renal function or peritonitis rates from the recently reported single-center UK study (12). It is also difficult to evaluate the relative benefit of using Balance in comparison with other practice patterns associated with reduced peritonitis rates.…”
Section: Caveatsmentioning
confidence: 99%
“…Proving that robust clinical benefits are associated with the use of the new solutions has been difficult (12), and a recent review commented that studies in the area have often been underpowered, of short duration, and focused on intermediate endpoints (13). Complicating matters further, the modern solutions are not identical with respect to their concentrations of GDPs (11).…”
mentioning
confidence: 99%